The Importance of Developing Gamification-Based Interactive Learning Media to Improve Disaster Mitigation and Preparedness Literacy Among Elementary School Students - Candra Kristiyan; Ani Rusilowati; Arif Widiyatmoko (Proceedings of International Conference on Science, Education, and Technology, 2026)
This study aims to determine the urgency of developing gamification-based interactive learning media for elementary school students in the context of disaster mitigation and preparedness literacy. Elementary school-aged children are in a phase of cognitive and psychomotor development that requires a contextual, participatory, and enjoyable learning approach. However, disaster education in elementary schools still tends to be theoretical, rote, and lacking in practical simulations. To optimize students’ understanding and preparedness, a revitalization of the learning approach is needed through the integration of gamification into interactive media. The method used in this study is a systematic literature review. This review begins with the research question: “Why is gamification-based interactive learning media necessary for disaster mitigation literacy in elementary schools?” Articles were searched for via Google Scholar, Scopus, ERIC, Springer, and ScienceDirect using the keywords: gamification, disaster literacy, interactive learning media, disaster mitigation and preparedness, and elementary schools (publication years 2022–2026). Based on the literature review, it was found that disaster mitigation education remains limited to the delivery of cognitive information; gamification has been proven to enhance student motivation, engagement, and memory retention; and interactive media enables safe and repeatable simulations of disaster scenarios. Therefore, theoretically grounded in scientific evidence, gamification-based interactive learning media need to be developed to strengthen disaster mitigation and preparedness literacy, as well as to foster responsive and adaptive habits among elementary school students in disaster-prone areas.